Comparison of Pre-Operative Blood Loss in Seropositive and Seronegative Pregnant Women Undergoing Elective Cesarean Section - Akbar, Amina; Zainab, Sadia; Mahboob, Saira; Zohra, Sadaf; Khan, Sadia; Parveen, Khalida (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the intraoperative blood loss and adhesions, peri-operative blood and intravenous iron supplementation between hepatitis seropositive and seronegative pregnant women undergoing elective cesarean delivery. Study Design: Cross-sectional, analytical study. Place and Duration of Study: Departments of Anesthesiology and Gynecology & Obstetrics, Combine Military Hospital, Okara Cantt Pakistan, from Oct 2018 to Mar 2019. Methodology: After approval of the hospital ethical committee, 134 (n=67 in each Group) pregnant women were included in our study by convenient sampling. Patients were divided into two groups. Group-A included seronegative pregnant women, whereas Group-B were seropositive pregnant women. Results: There was no difference in the age (p=0.357), gravidity (p=0.159), parity (p=0.226) and the number of cesarean sections (p=0.475) between the two groups. There was no difference in the two groups regarding peri-operative haemoglobin change,with an insignificant reduction of 0.60±1.21 g/dL in Group-A versus a reduction of 0.50±1.08 g/dL in Group-B. A mild level of adhesion was observed intraoperatively in 26(35.6%) in Group-A versus 27(37.5%) in Group-B; p=0.170. Mild difficulty securing hemostasis was reported in 25(34.2%) vs 29(40.2%) patients; p=0.329. 61(83.5%) did not require a peri-operative blood transfusion in Group-A versus 59(81.9%) in Group-B; p=0.528. Conclusion: Our study has shown that the peri-operative haemoglobin level, blood product and intravenous iron supplementation, intra-operative adhesions encountered, and difficulty in hemostasis were comparable between sero-positive and sero-negative viral hepatitis pregnant women.